2018
DOI: 10.1186/s12991-018-0202-6
|View full text |Cite|
|
Sign up to set email alerts
|

Depression during pregnancy and preterm delivery: a prospective cohort study among women attending antenatal clinic at Pumwani Maternity Hospital

Abstract: BackgroundPreterm birth occurs among 9.6% of births worldwide and is the leading cause of long-term neurodevelopmental disabilities among children and also responsible for 28% of neonatal deaths. No single etiological factor is responsible for preterm birth, but various risk factors have been identified. Prior studies have reported that compromised maternal mental health occurring during pregnancy may lead to various adverse obstetric outcomes.ObjectiveTo determine whether antenatal depression is significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 26 publications
1
30
3
Order By: Relevance
“…In Zimbabwe, recent studies have also shown that intimate partner violence is a risk factor for depression in the perinatal period [22,39]. Unlike other studies in LMICs [5,12,13,17,18,21,40], we did not find any significant associations of antenatal depression with HIV, maternal age, educational level, history of obstetric complications, social support and gravidity. This may be due to methodological differences.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In Zimbabwe, recent studies have also shown that intimate partner violence is a risk factor for depression in the perinatal period [22,39]. Unlike other studies in LMICs [5,12,13,17,18,21,40], we did not find any significant associations of antenatal depression with HIV, maternal age, educational level, history of obstetric complications, social support and gravidity. This may be due to methodological differences.…”
Section: Discussioncontrasting
confidence: 99%
“…depression in women from Sub-Saharan Africa ranges from 20 to 49% [5,[12][13][14][15][16][17][18][19][20][21][22][23]. These prevalence variations can be explained by several reasons.…”
mentioning
confidence: 99%
“…Presence of periodontal disease (AOR 2.32; 95%CI: 1.33-4.27) [34] and periodontitis (at least three sites from different teeth with clinical attachment loss greater than or equal to4 mm [85] was significantly associated with PTB. Maternal depression increased the probability of having PTB (ARR 4.13; 95% CI: 2.82-17.42) [65]. Hematocrit level < 33 (AOR 7.2; 95% CI: 3.1-16.8) [63] and presence of chronic illness (AOR 4.5; 95% CI: 2, 10.2) [63] were found to be significantly associated with PTB.…”
Section: Medical Conditionsmentioning
confidence: 99%
“…, 11 from Ethiopia[52][53][54][55][56][57][58][59][60][61][62][63], 6 from Kenya[5,54,[64][65][66][67], 7 from Malawi [4, 6, 68-72], 3 from Sudan [10, 73, 74], 3 from Zambia [75-77],3 from Zimbabwe [78-80], 2 from Uganda [7, 81], 2 from Mozambique[82,83], 1 from Rwanda[84], and 1 from Madagascar[85]. Twenty five studies were done by cohort study design[33, 35, 36, 39, 41, 43, 45-50, 59, 61, 65-68, 70, 75, 77, 80, 83-85], 9 studies by case control study design[7,10,37,38,53,55,57,73,79] and 24 studies by cross sectional study design[4-6, 34, 40, 42, 44, 51, 52, 54, 56, 58, 60, 62, 64, 69, 71, 72, 74, 76, 78, 81, 82] (Table 1).…”
mentioning
confidence: 99%
“…Following the publication of the original article [ 1 ], the authors reported the following typesetting errors:…”
Section: Correction To: Ann Gen Psychiatry (2018) 17:31 101186/s1299mentioning
confidence: 99%